TINJAUAN HUKUM ISLAM TERHADAP TRADISI PERHITUNGAN WETON SEBAGAI ACUAN DALAM PERNIKAHAN (STUDI KASUS MASYARAKAT JAWA DI DESA SINGA GEMBARA) - Hartono, Hartono; Fahruddin, Achmad; Prihatin, Titi (Islamic Family Law, STAI Sangatta Kutai Timur, 2025)
Indonesia's cultural richness, especially Javanese traditions, demands sustainable preservation. One of the traditions that is still strongly adhered to is the calculation of weton as a reference in marriage. This study aims to analyze the practice of calculating weton in Singa Gembara Village from the perspective of Islamic law, as well as identify problems and solutions that can be applied. The research method used is qualitative descriptive with a field study approach, through observation and interviews with the local Javanese community. The results of the study show that people are still very attached to the weton tradition in determining the compatibility of couples and the good day of the wedding, although the calculation methods vary. In the view of Islamic law, this practice is acceptable as 'urf as long as it is not believed to be the absolute determinant of fate or to associate with Allah. However, excessive dependence on weton can cause problems such as marriage annulment, family conflicts, and the potential erosion of faith. Therefore, it is necessary to strengthen religious education about destiny, develop Islamic-based premarital guidance, a balanced cultural approach, and counseling services. This study recommends the integration of local cultural preservation and sharia obedience as a path to a harmonious marriage and according to Islamic guidance.